Implementing supply chain visibility to promote fisheries sustainability - Almeida, I. D. de.; Silva, J. M. V.-B. da.; Ferreira, L. M. D. F.; Harjivan, C. K. (17th Cambridge International Manufacturing Symposium. Disruptive supply network models in future industrial systems: Configuring for resilience and sustainability. Symposium Proceedings, 2013)
Operationalising good practices and better management of marine resources were pursued, in a retailer exploratory case, by following a triple bottom line approach to fine tuning corporate responsibility. Recommendations towards sustainable operations were made, as regards: developing voluntary self-certification towards eco-labelling based on third party; using IT, as a transparency promoter and so, as a leverage for traceability, collaboration and trust across the chain of custody; designing customised policies to deal with different consumer profiles and so, assuring their loyalty by adjusting consumer campaigns; educating consumers as seafood demand regulators. Improvements in Greenpeace evaluation were documented, profit increase was expected.